PROYECTO DE FACTIBILIDAD PARA LA PRODUCCIÓN Y COMERCIALIZACIÓN DE SALSA PICANTE DE YUCA EN LA CIUDAD DE LOJA. - Encarnación Vega, Margorie Janeth (2024)
The general objective of the research work on the production and commercialization of cassava hot sauce in the city of Loja is to conduct a financial evaluation to determine its feasibility or not. The type of research is descriptive exploratory with a qualitative and quantitative non- experimental approach, taking into consideration the different methods, techniques, and research instruments for the collection of the necessary information. The results that allowed determining the feasibility of the project are based on the Net Present Value (NPV) of $15. 809.98 being positive, the Internal Rate of Return (IRR) of 59.74% which is higher than the opportunity cost of 11.25%, the Capital Recovery Period, which is 1 year, 10 months, and 25 days, the Cost-Benefit Ratio (CBR) which is 0.18 US cents which means that the company will obtain for every dollar invested, concerning the sensitivity analysis we have to support a decrease in revenue of 7.22% and the increase in costs of 8.44%.